Making Promotional Media through YouTube at the Bantengan Turangga Jaya Art Group, Wiyu Village, Pacet District, Mojokerto Regency - Indar Sabri; Koko Hari Pramono; Mujib Alfirdaus (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2022)
The Wiyu village's traditional arts have not developed or made much progress in the last two years since the outbreak began. As one of the reinforcements of the village, this traditional art must be revived so that the tourist village can be re-run with more varied programs. For instance, in the form of incentive tourism locations where the village potential is fully developed to support the success of the existing tourist destinations. One of the bantengan arts groups that requires special attention in order to compete is Turangga Jaya, which is located in Wiyu Village, Pacet Subdistrict, and Mojokerto Regency. In this case, researchers packaged the performances for welcoming and also created a Youtube channel as a means of promotion and documentation to increase marketing success. It is necessary to use promotional materials as part of a marketing strategy to connect with art enthusiasts so that the younger generation knows about it. This art will have viewers among the younger generation if it can use social media as a promotional tool. Thus, to assist the survival of the Turangga Jaya bantengan art, this community service strategy was implemented.